2019
DOI: 10.3390/economies7020031
|View full text |Cite
|
Sign up to set email alerts
|

Economic Reforms, Labour Markets and Formal Sector Employment: Evidence from India

Abstract: Development economists generally concur that the implications of economic reform for employment are influenced by an economy’s institutional framework. This paper examines the extent to which differences in regional labour market flexibility shaped the impact of unanticipated economic reforms on employment in formal manufacturing firms in India in the 1990s, using pooled cross-sectional firm survey data. It employs a difference-in-differences strategy for this analysis and finds that, on average and ceteris pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Fourteen studies were conducted in developed countries, namely the United States, the United Kingdom, Brazil, South Korea, Lithuania, Russia, Australia and Slovenia (Autrey et al, 2014;Williams & Harodnik, 2015a;Williams & Harodnik, 2015b;Kim & Kim, 2016;Visser, 2017;Abdel-Latif et al, 2017;Milovanova et al, 2018a;Milovanova et al, 2018b;Kireenko & Nevzorova, 2019;Keen & Ride, 2019;Navickas et al, 2019;Fedotov et al, 2020;Bayar et al, 2020). In developing countries, 12 research have been identified to be relevant with effects of the informal economy towards employment, namely Malaysia, Brazil, South Africa, Turkey, Croatia, India, Pakistan, Indonesia and Colombia (Bosch & Pretel, 2015;Tijdens & Besamusca, 2015;Rothenberg et al, 2016;Williams & Franic, 2016;Elveren & Osgur, 2016;Tan et al, 2016;Shembavnekar, 2019;Dominguez, 2019;Ullah et al, 2019;Avenyo et al, 2020;Santoso & Sriyana, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were conducted in developed countries, namely the United States, the United Kingdom, Brazil, South Korea, Lithuania, Russia, Australia and Slovenia (Autrey et al, 2014;Williams & Harodnik, 2015a;Williams & Harodnik, 2015b;Kim & Kim, 2016;Visser, 2017;Abdel-Latif et al, 2017;Milovanova et al, 2018a;Milovanova et al, 2018b;Kireenko & Nevzorova, 2019;Keen & Ride, 2019;Navickas et al, 2019;Fedotov et al, 2020;Bayar et al, 2020). In developing countries, 12 research have been identified to be relevant with effects of the informal economy towards employment, namely Malaysia, Brazil, South Africa, Turkey, Croatia, India, Pakistan, Indonesia and Colombia (Bosch & Pretel, 2015;Tijdens & Besamusca, 2015;Rothenberg et al, 2016;Williams & Franic, 2016;Elveren & Osgur, 2016;Tan et al, 2016;Shembavnekar, 2019;Dominguez, 2019;Ullah et al, 2019;Avenyo et al, 2020;Santoso & Sriyana, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the aggressive shift toward neoliberalism there is a documented increase in the informal workforce in India, referred to as the 'precariat' (Balasubramanian & Sarkar, 2020;Standing, 2014Standing, , 2018. Today, permanent workers in India who are only 8% of the total workforce are collectively agreeing at the plant, enterprise, industry, sectoral and national levels, whereas the country beholds the existence of a mix of informal and unorganised workers accounting for 92% of the total workforce with outright no bargaining power (Breman, 2013;Shembavnekar, 2019). The coal sector gradually echoed a similar composition of the workforce where a permanent worker received protection from regulations, unions and possibly coverage under collective bargaining (Balasubramanian et al, 2023;Sarkar, 2019), whereas informal workers lost out on benefits of collective bargaining, regulatory protections and decent work.…”
Section: Germane Literaturementioning
confidence: 99%
“…However, the declining unionisation rates were not equal and similar in all industrial sectors and there have been some exceptions that need further investigation. Neoliberal reforms have not been successful in bringing one single pattern of changes in IR in India because union density declined even when India witnessed employment growth with the government pushing up the frontiers of economic recovery after 1991 (Nagaraj, 2004; Shembavnekar, 2019). Policy reforms such as attracting investors, turning cash holdings into investments and dis‐investment of state‐operated enterprises (SOEs) drove the economic revival (Rhodes, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to reverse this productivity decline, a few reforms were initiated in the 1980s that proved inadequate in the face of growing fiscal and external macroeconomic imbalances. 7 Further, a spike in oil prices owing to the Gulf War, a decline in remittance inflows from the Middle East, political uncertainty, and a drop in demand for exports to major trade partners led to a balance-of-payments crisis in 1990-1991, which compelled the government to seek help from the International Monetary Fund. The Fund agreed to provide support, conditional on the government undertaking a series of macrostructural reforms, and India finally liberalized its economy in 1991.…”
Section: Historical and Political Context Of Internal Migration In Indiamentioning
confidence: 99%
“…The Fund agreed to provide support, conditional on the government undertaking a series of macrostructural reforms, and India finally liberalized its economy in 1991. 7 The neoliberal ideology asserted that higher and sustained economic growth should be the state goal and, in order to achieve that, the state should not interfere with any economic activity. Further, it postulated that economic reforms would accelerate growth, as well as employment rates and wages in developing countries, after which working conditions and socioeconomic circumstances of the poor and vulnerable workers would improve.…”
Section: Historical and Political Context Of Internal Migration In Indiamentioning
confidence: 99%